Os estados e a ordem internacional contemporânea: Atas do V Encontro Luso-Espanhol de Professores de Direito Internacional e Relações Internacionais - José Juste Ruiz (Investigação, 2019)
The statecentric perspective, enrooted in the European modernity, has been at the heart of the mainstream discourse on the international system. However, it needs a sharper view on the diversity of concrete states and on the impact of that heterogeneity in the contents and scope of international law. This has been the aim of the 5th Portuguese-Spanish Meeting of Professors of International Law and International Relations and of this book. Different approaches on the political and institutional conditions of international law and of its enforcement are to be found here. The papers presented to the 5th Meeting show the up-to-dateness of the work of Francisco de Vitoria and it focus on the notion of totus orbis as the main reference of international legality. This book gathers different forms of questioning that modern ideal, all of them based upon the reality of concrete states' heterogeneity.